Exercise ameliorates the detrimental effect of chloroquine on skeletal muscles in mice via restoring autophagy flux - Jiang Dan; Chen Kai; Lu Xuan; Gao Hong-jian; Qin Zheng-hong; Lin Fang (Acta Pharmacologica Sinica, 2016)
Dan JIANG1, #, Kai CHEN2, #, Xuan LU1, Hong-jian GAO3, Zheng-hong QIN1, Fang LIN1, * 1Department of Pharmacology, Laboratory of Aging and Nervous Diseases (SZS0703), Soochow University School of Pharmaceutical Science, Suzhou 215123, China; 2 Department of Cancer, the First Affiliated Hospital of Soochow University, Suzhou 215006, China; 3Electron Microscopy Core Laboratory, Shanghai Medical College, Fudan University, Shanghai 200032, China Aim: To study the roles of autophagy in muscle establishment during long-term exercise in mice. Methods: Female ICR mice were submitted to exercise training with a wheel running regimen: 6 m/min, 15 min/time, 3 times/d (on 8:00, 14:00, and 20:00), 5 d/week for 2 months. The mice were treated with the autophagy activator trehalose (1% aqueous solution as a daily drinking water) or the autophagy inhibitor chloroquine (10 mg/kg, ip, 5 times a week) before the training. Western blotting analysis, TUNEL staining, H&E staining and transmission electron microscope were used to evaluate the activity of autophagy and the structure of the muscle fibers. Results: The exercise training significantly stimulated the formation of autophagosomes, increased the LC3-II, cathepsin L and Bcl-2 levels, lowered the P62 level and increased the antioxidant capacity in the muscles. Meanwhile, the exercise training significantly improved the morphology of mitochondria, reduced the release of cytochrome c from mitochondria to cytoplasm, and slightly decreased the apoptosis rate in the muscles. Administration of trehalose increased the level of autophagy and protected the muscle fibers from apoptosis. Administration of chloroquine blocked autophagy flux and exerted detrimental effects on the muscles, which were ameliorated by the exercise training. Conclusion: Long-term regular exercise activates autophagy process associated with muscle establishment, and ameliorates the detrimental effects of chloroquine on skeletal muscles via restoring autophagy flux. Keywords: autophagy; skeletal muscle; exercise; apoptosis; mitochondria; trehalose; chloroquine We are grateful to Dr Fiona M MENZIES for her careful revision and critical comments on this paper. This work were supported by grants from the Priority Academic Program Development of Jiangsu Higher Education Institutions (PADA) and Jiangsu Key Laboratory of Translational Research and Therapy for Neuro-Psycho-Diseases and College of Pharmaceutical Sciences, Soochow University, China (BM2013003). # These authors contributed equally to this article. * To whom correspondence should be addressed. E-mail bluestonelin@hotmail.com Received 2013-04-14 Accepted 2013-08-28